Developing Physics Learning Tools of Blended Learning Using Schoology with Problem-Based Learning Model - Dwi Ulan Rahmawati; Jumadi Jumadi; Eko Mhd Ramadan (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
This study is a development of research that aimed to (1) produce Physics learning tools based on blended learning that are suitable to be used in learning, and (2) determine the quality of learning tools that had been developed. This study used a 4D model, consisting of the defining, designing, developing and disseminating. The learning tools that had been developed consisted of Syllabus, Lesson Plan (RPP), Student Worksheet (LKPD), Handouts, and Learning Media of Web Schoology. The results of the development of learning tools established were included in the “excellent category” based on qualitative and quantitative assessments from expert lecturers, Physics teachers and peers with an average score of around 95 – 98. In addition, the testing of learning tools was carried out to 33 students that showed an average score of students’ response of 77.51, which was included in a “good category”, used in the learning process of large – scale field tests. Furthermore, each phase of the implementation of the lesson plan was categorized very well for each meeting with the achievement of the score of observations of around 80% - 100%.